Evaluation of the bactericidal effect of Nisin and /or Potassium sorbate and Sodium chloride on the viability of Staphylococcus aureus in soft cheese: Zina Saab Khudhir and Adnan Jawad Ahmed - Ahmed, Adnan Jawad (The Iraqi Journal of Veterinary Medicine, 2017)
Effect of different concentrations of Nisin, Potassium sorbate and Sodium chloride on the keeping quality of the locally produced soft cheese samples against the Staphylococcus aureus viability was conducted during November 2015/ May 2016. Staphylococcus aureus were isolated from 20(73.33%)out of 30 bovine and ovine locally produced soft cheese samples and their identification were confirmed based on the morphological, rapid biochemical reactions and serological properties. Staphylococcus aureus isolates that obtained by plating on the Chromogenic agar were further tested serologically. The highest significant (P<0.05) prevalence levels of Staph aureus were found in the cow's soft cheese samples 8/10(80%) followed by both ewe's and buffalo's soft cheese samples7/10 (70%) respectively. Three concentrations for each of Nisin, Potassium sorbate and Sodium chloride (50, 25 and 12.5 IU/ml), (0.4, 0.2 and 0.1%) and (10, 5 and 2.5) were used respectively. The minimum inhibitory concentrations of the Nisin and both Sodium chloride and Potassium sorbate against Staphylococcus aureus that were determined by the turbid metric technique were 50 IU/ml, 10% and 0.4% respectively. Mean values (log c.fu/ml) of the starting initial Staph aureus counts in the experimentally manufactured soft cheese samples decreased significantly (P<0.05) from 7.00±0.002 (log c.fu/ml) at 0 hour to 5.11±0.039 (log c.fu/ml) after 24 hrs of exposure to action of Nisin and Potassium sorbate inside the brine solution at 37°C. The bactericidal activities of Nisin and Potassium sorbate were more effective than either of them alone after 24 hrs. of exposure inside the brine solution at 37°C (reduction level approximately 3 log cycles), but the bacterial counts still were above the safe limit, which is required for the production of Staph aureus enterotoxin.